2022
DOI: 10.1111/aphw.12415
|View full text |Cite
|
Sign up to set email alerts
|

The temporal effect of emotional distress on psychological and physical functioning in endometriosis: A 12‐month prospective study

Abstract: Psychological factors of emotional distress and cognition have an important role in the understanding and management of endometriosis; however, their temporal relationship with key pain variables is not fully understood. This exploratory study sought to establish the temporal relationship between psychological and pain‐related factors in a 12‐month prospective study of 208 Australian women with endometriosis. Participants, aged 18–50 years and living in Australia, were recruited via social media and completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
0
0
Order By: Relevance
“…Certain studies suggest that psychological factors like anxiety and depression may adversely impact the physiological functions of endometriosis. [41,42] Further research has shown that individuals diagnosed with endometriosis exhibit a higher prevalence of anxiety and depression compared to their counterparts in control groups. [43,44] However, these investigations are constrained by their inability to establish a definitive causal link between anxiety, depression, and endometriosis, thus limiting their conclusions to mere correlations.…”
Section: Discussionmentioning
confidence: 99%
“…Certain studies suggest that psychological factors like anxiety and depression may adversely impact the physiological functions of endometriosis. [41,42] Further research has shown that individuals diagnosed with endometriosis exhibit a higher prevalence of anxiety and depression compared to their counterparts in control groups. [43,44] However, these investigations are constrained by their inability to establish a definitive causal link between anxiety, depression, and endometriosis, thus limiting their conclusions to mere correlations.…”
Section: Discussionmentioning
confidence: 99%